Desirability functions as response in a d‐optimal design for evaluating the extraction and purification steps of six tranquillizers and an anti‐adrenergic by liquid chromatography‐tandem mass spectrometry. (23rd December 2015) - Rubio, Laura; Oca, María Leticia; Sarabia, Luis; García, Inmaculada; Ortiz, María Cruz
Abstract: Internal standards can be added at different stages of an analytical procedure. When they are added at the beginning of a multiresidue method and their behavior is not exactly the same as that of the analytes, the intended correction for small variations within the analytical process could not be achieved. Because of this, in the present work, the use ofd ‐optimal designs together with desirability functions is proposed to state the experimental response under study. The overall desirability function used relates two analytical criteria: to assess a similar chemical behavior of each analyte in relation to its internal standard and to avoid a significant reduction of the absolute peak area of the internal standards. This strategy has been applied to the analysis of the effect of four factors related to the extraction and purification steps of six tranquillizers and a β ‐blocker from pig muscle analyzed by liquid chromatography–tandem mass spectrometry. The effect of those factors has been evaluated by means of an ad hoc d ‐optimal design consisting of only 11 experiments. The resulting levels of the four factors that enable to achieve the greatest overall desirability have also been compared with those obtained when either the standardized or absolute peak area has been considered as response. Differences in both the significant factors and their optimum levels have been observed. It is noticeable that the experimental effort necessary to study the effect of the factors has been reduced by more than 50% thanks to thed ‐optimal design. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : A novel use of desirability functions together withd ‐optimal designs in the analysis of the effect of four factors related to the extraction and purification steps of seven drugs in pig muscle tissue analyzed by liquid chromatography–tandem mass spectrometry following the criteria in Commission Decision 2002/657/EC is proposed. As the pretreatment steps might affect the analyte and the internal standard in a different way, the conclusions drawn about the optimum level of every factor are different depending on the response variable considered.